2014
DOI: 10.2139/ssrn.2530987
|View full text |Cite
|
Sign up to set email alerts
|

Two Stage Exits: An Empirical Analysis of the Dynamic Choice between IPOs and Acquisitions by European Private Firms

Abstract: A private firm's exit decision has been modeled in the existing empirical literature as a dichotomous choice between IPO and acquisition. In this paper, we take a dynamic approach and analyze how explicitly accounting for dynamic considerations, such as the benefits arising from being acquired after going public at higher valuations relative to a direct acquisition, or the costs arising from being delisted at lower valuations, alters the initial IPO vs. acquisition trade-off. We find that firms that are more v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…When we focused on the ESG issue components, the results were in line with the former of ESG issues, indicating a higher probability of delisting, from 20% to 38.6%, in the manufacturing sector for governance and social reputation exposure. This was consistent with the view that weak firms in product markets have a greater likelihood of delisting (Chemmanur et al, 2019). Overall, our results showed that governance and social issues in the manufacturing industry play an important role in firms' delisting.…”
Section: Controlling For Service -Manufacturing Industries and Crisis Periodssupporting
confidence: 92%
“…When we focused on the ESG issue components, the results were in line with the former of ESG issues, indicating a higher probability of delisting, from 20% to 38.6%, in the manufacturing sector for governance and social reputation exposure. This was consistent with the view that weak firms in product markets have a greater likelihood of delisting (Chemmanur et al, 2019). Overall, our results showed that governance and social issues in the manufacturing industry play an important role in firms' delisting.…”
Section: Controlling For Service -Manufacturing Industries and Crisis Periodssupporting
confidence: 92%
“…A firm's innovative capabilities improve long-term performance and shape a firm's exit decisions Marsili 2012, 2019). Chemmanur et al (2014b) found that compared to IVC-backed firms, CVC-backed firms are more innovative, younger, riskier and less profitable. However, the authors also suggest that CVCs are better able to nurture innovation because of the technological fit of their parent companies with the entrepreneurial firms they back and because of their greater tolerance for failure compared with their IVC counterparts.…”
Section: Delisting Through a Failure And The Type Of Vc Investormentioning
confidence: 99%
“…Thus, distinguishing between intra-and extra-EU deals is more appropriate in order to understand the forces at stake. We consider first the impact of VCs in post-IPO acquisition in a general way, by The literature has identified several types of assets and characteristics that make firms more likely to become acquisition targets shortly after their IPO (Jain and Kini 2000;Brau et al 2010;De and Jindra 2012;Chemmanur et al 2014b). However, these studies have little to say on differences across domestic and cross-border transactions.…”
Section: Delisting Through Mandas and The Type Of Vc Investormentioning
confidence: 99%
See 1 more Smart Citation